Severe obstructive sleep apnoea is independently associated with pulmonary artery dilatation. Issue 7 (23rd September 2013) - Kawano, Yoshiyuki; Tamura, Akira; Watanabe, Toru; Kadota, Junichi
Abstract: Background and objective: We hypothesised that obstructive sleep apnoea (OSA) may cause pulmonary artery dilatation through excessively negative intrathoracic pressure generated during inspiratory efforts against the upper airway collapse during obstructive apnoeas. To test this hypothesis, we examined the association between OSA severity and pulmonary artery dilatation. Methods: A total of 173 patients who were clinically suspected of having OSA underwent chest radiography and polysomnography. We measured the right descending pulmonary artery diametre (RDPAD) on the chest radiogram and defined an abnormal increase in the RDPAD as RDPAD > 16 mm in males and RDPAD > 15 mm in females. Results: An abnormal increase in the RDPAD was more prevalent in patients with severe OSA (46.3%) compared to those with no or mild OSA (14.5%) and those with moderate OSA (21.6%). A univariate logistic regression analysis showed that severe OSA was associated with an abnormal increase in the RDPAD (odds ratio 3.94, 95% confidence interval 1.98‐7.87). After controlling for age, gender, body mass index, smoking history and partial pressure of arterial oxygen, severe OSA still remained significantly associated with an abnormal increase in the RDPAD (odds ratio 4.06, 95% confidence interval 1.82–9.07). Conclusions: Severe OSA is independently associated with an abnormal increase in the RDPAD, suggesting that severe OSA may cause pulmonary artery dilatation. Abstract : We examined the association between the severity of obstructive sleep apnoea (OSA) and the right descending pulmonary artery diameter (RDPAD) on the chest radiogram and found an independent association between severe OSA and an abnormal increase in the RDPAD, suggesting that severe OSA may cause pulmonary artery dilatation.